ANALYSIS OF STUDENTS' UNDERSTANDING OF CONCEPTS IN SUBSTANCES AND THEIR CHANGES AT SMPN 2 SOCAH - Berlian Ari Andani (Prodi Pendidikan IPA FMIPA Universitas Negeri Malang, 2023)
This research analyzes students' conceptual understanding of substances and their changes using test answers as the leading indicator. Each question indicator is assessed and broken down based on the students' conceptual understanding percentage, with completeness set at an average score of ≥ 70. Of the 13 research subjects, almost all students reached the level of completeness, with a percentage of students completing at 87.7%, while students who have not yet reached completeness at 12.3%. This shows an excellent overall understanding of the concept. However, several students had difficulty understanding the difference based on the location of the particles, which may have been influenced by a lack of attention to the teacher's explanation. Understanding the concept of chemical and physical changes reached an average of 83%. Although most students could identify chemical changes, some were still confused and did not pay attention to the characteristics of chemical changes. Understanding the concept of physical changes also needs to be improved, with some students assuming that physical changes involve the formation of new substances. The understanding of the concept of mixture separation reached 90%, indicating that students can explain mixture separation experiments. Overall, SMPN 2 Socah seventh grade students showed.